Examining the Influence of Digital Learning on Women's Education in Afghanistan: An In-Depth Analysis of Women Online University - Quraishi, Tamanna; Ayeshan HASHIMI; Susan YASINI; Parisa BARAK; Zahra AMANI; Sara Afif SAHEL (RADINKA JAYA UTAMA PUBLISHER, 2024)
The research aims to address the pressing need for innovative approaches to overcome barriers to education faced by Afghan women, particularly in regions with limited access to traditional learning resources. The study employs a systematic research method, beginning with a thorough review of the literature to establish the context and theoretical framework surrounding e-learning in Afghanistan. It explores the transformative potential of e-learning in empowering Afghan women, while also examining the challenges hindering its implementation. A stratified random sampling technique was utilized to select a representative sample of 150 female students from the Women Online University in Afghanistan. This sample size was deemed sufficient to obtain comprehensive insights into the perspectives and experiences of female students regarding e-learning. Data was collected through structured surveys, designed to assess various aspects of e-learning effectiveness, challenges, and empowerment. Quantitative data analysis techniques, including descriptive statistics and frequency distributions, were employed to analyze the survey responses. The findings reveal insights into the demographic distribution of female students at Women Online University, the distribution of online platforms used for e-learning, challenges in implementation, and perceptions of empowerment. Through a rigorous analysis of the data, this study aims to provide valuable insights into the current landscape of e-learning for female education in Afghanistan. The results contribute to a deeper understanding of the opportunities and challenges associated with e-learning initiatives, while also offering recommendations for policymakers, educators, and stakeholders to enhance the effectiveness and accessibility of e-learning for Afghan women.